Sediment elemental composition (XRF) of sediment core GeoB19973-2 - Jens Weiser; Dierk Hebbeln (PANGAEA, 2025)
XRF Core Scanner data of sediment core GeoB19973-2 from Baffin Bay were collected every two centimetres downcore over an active area of 15 mm^2 with a downcore slit size of 10 mm using generator settings of 10 and 30 kV directly at the split core surface of the archive half with XRF Core Scanner II (AVAATECH Serial No. 2) at MARUM, Bremen.